2013
DOI: 10.1016/j.clml.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical Trial of Valacyclovir and Standard of Care Cyclophosphamide in Children With Endemic Burkitt Lymphoma in Malawi

Abstract: Treatment options for Epstein-Barr virus (EBV)-associated Burkitt lymphoma in Africa are limited because of chemotherapy-associated toxicity. Since other EBV-associated diseases respond to antiviral agents, we investigated adding an antiviral agent, valacyclovir, to the current chemotherapy regimen in Malawi. In this phase I safety study, we showed that cyclophosphamide combined with valacyclovir was safe. Phase II efficacy trials should now be undertaken. Background Nucleoside analogues, including acyclovir,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“… 43 On the basis of this proposition, a phase I study recently evaluated the concomitant use of valacyclovir and cyclophosphamide in endemic Burkitt lymphoma and showed that this combination was safe. 44 Further clinical testing of this concept is needed.…”
Section: Methylation Of Ebv Genome As a Potential Therapeutic Targetmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 On the basis of this proposition, a phase I study recently evaluated the concomitant use of valacyclovir and cyclophosphamide in endemic Burkitt lymphoma and showed that this combination was safe. 44 Further clinical testing of this concept is needed.…”
Section: Methylation Of Ebv Genome As a Potential Therapeutic Targetmentioning
confidence: 99%
“…Except when used together with epigenetically active agents, 41 , 42 , 43 , 44 antiviral drugs exhibit no direct effect on EBV+ LPD. However, when used prophylactically, antiviral drugs appear to suppress EBV replication and hence decrease the occurrence of PTLD after HSCT or solid organ allografting.…”
Section: Antiviral Treatment In Ebv+ Lpdmentioning
confidence: 99%
“…In answering (1), valacyclovir was used successfully mostly in combination with other therapies, and on grounds of immune dysregulation— including post-transplant patients, HIV, etc— in EBV-related cases of encephalitis/various forms of CNS infection,36 37 severe/complicated (eg, with hepatic involvement)/chronic infectious mononucleosis,38 hepatitis,39 chronic fatigue syndrome,40 hairy leukoplakia,41 hydroa vacciniforme,42 various types of LPDs (eg, Burkitt lymphoma),43 oral papulosis,44 periodontitis45 and lymphocytic myocarditis 46. For these conditions, which may coexist, other antiherpetics have also been used.…”
Section: Discussionmentioning
confidence: 99%